Pengembangan Pemodelan Ontologi Semantik dalam Representasi Pengetahuan Instrumen Gamelan Bali - Wardana, Made; Pramartha, Cokorda Rai Adi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
Indonesia has many types of cultural and artistic heritage, which one is Balinese gamelan. Knowledge of Balinese gamelan still tends to be less explicitly collected. This result the cultural heritage knowledge, especially the Balinese gamelan challenging to be learned by the young and future Balinese generation. Therefore, the knowledge of Balinese gamelan information should be documented well, especially in the digital form. In this research, we develop an ontology for Balinese cultural heritage, specifically the gamelan Bali. This ontology can be used to capture, document, and represent knowledge surrounds the Balinese gamelan domain. The construction of the ontology model was carried out using the Methontology methodology. The gamelan ontology has 112 classes, 31 datatype properties, 53 object properties, and 289 instances. Further research needs to carry out in order to evaluate and improve the quality of ontology, and follow-up by the implementation into a semantic web-based application.